Indigenous Knowledge-Sharing Interventions in Australia and the Use of Information and Communication Technology: A Scoping Review - Gregor, Shirley; Gunawardena, Maya; Imran, Ahmed; Okai-Ugbaje, Safiya; Page Jeffery, Catherine; Wilson, Rhonda (Australasian Journal of Information Systems, 2023)
Indigenous peoples in Australia are subject to significant disadvantages both socio-economically and in health, education and service provision. Knowledge-sharing interventions, including those with an information and communications technology (ICT) base, have the potential to address these challenges. Interventions occur against a background of an ancient culture with distinctive ways of knowing and doing, including storytelling, art and performance. This study documents the results of a scoping review of interventions that have been undertaken in this context. It considers the outcomes of these interventions, the extent to which Indigenous ways of knowing were accounted for and whether ICT was involved. Our review of the peer-reviewed literature located two prior reviews and seven primary studies. All of the primary studies were about health interventions; of these, all those that reported positive outcomes only had incorporated Indigenous ways of knowing, some in innovative ways. Only two studies used ICT as their main vehicle. This article provides a base for further work by documenting the current status of the field and identifying the gaps, such as the scarcity of non-health and ICT-based studies. The cases identified provide useful insights for those with an interest in developing future initiatives.